Analisis Financial Distress pada Perusahaan Sub Industri Penerbangan dan Kereta Api yang Terdaftar di Bursa Efek Indonesia Sebelum dan Sesudah Pandemi Covid-19 - Elvina Gunawan; Debbianita Debbianita (Universitas Kristen Maranatha, 2022)
The Covid-19 pandemic has impacted all fields, including the airline and railway industries. One of the impacts is the decrease in passengers causes the company's income to decline. This condition can make the companies face financial difficulties, which can end in bankruptcy. This research aims to analyze the financial distress in the sub-industry companies before and after the Covid-19 pandemic, especially in the airline and railway industries listed on the Indonesian stock exchange using the Altman Z-Score and Springate methods. The type of research used is descriptive quantitative with purposive sampling technique in taking the samples. Data are collected by applying the documentation technique with secondary data in quarterly financial reports from 2018 to 2021. The research sample amounted to four companies. The research shows that the Altman Z-Score and Springate methods used in the analysis of financial distress before and after the Covid-19 pandemic in four companies present the same results in which the companies entered a dangerous zone because of the decline in the income. Future research is recommended to use other methods to analyze financial distress and expand the research population or other companies. Keywords: The Covid-19 Pandemic, Financial Distress, Altman Z-score, and Springate